Perancangan Fasilitas Kerja Proses Pengelasan yang Ergonomis dengan Menggunakan Metode Design For Manufacture And Assembly (DFMA) di Bengkel Las Wen - Nofirza Nofirza; Anwardi Anwardi; Rika Rika; Fajar Sidik Rudini (Performa: Media Ilmiah Teknik Industri, 2019)
The "wen" welding workshop business does welding with bad work postures that cause muscle injury (Musculoskeletal Disorders). For this reason, it is necessary to design a work facility for an efficient welding process. The Nordic Body Map (NBM) questionnaire was used to find out which body parts had complaints that they were not sick, enough pain, illness and evaluation using the Rapid Entire Body Assessment (REBA) method to become an input to improve the operator's work posture to be better. The design of welding facilities is carried out using the Design For Manufacture and Assembly (DFMA) method because it can evaluate the costs and material of new design facilities with pre-existing design facilities in the testing phase. The design results are in the form of a workbench that has a footrest, a welding wire, a material laying place, a bow and vise in a facility, based on testing the lower the REBA score results so that the work posture is better, the facility can be used to weld all products to the workshop weld and efficiency compared to the previous tool at 35%.